Strategi Penanganan Bencana Banjir Di Wilayah Rawan Banjir : Studi Kasus Di Banjarmasin - Natasya Zahwa Lestari; Rosalina Kumalawati (Universitas PGRI Palembang, 2024)
The city of Banjarmasin is highly vulnerable to flooding due to its low-lying geographical conditions, numerous rivers, and significant projections of sea level rise. This study aims to examine the geographical and hydrological factors contributing to flood vulnerability in Banjarmasin, analyze the impacts and flood-affected areas, and evaluate sea level rise projections and the flood management strategies that have been implemented. The research employs a descriptive qualitative method to investigate the causes of flooding and the corresponding mitigation strategies. The findings indicate that flooding is caused by both natural factors and human activities, such as river pollution due to waste and poor drainage systems. Community participation remains low and tends to be seasonal. Flood mitigation efforts need to be strengthened through improved infrastructure, continuous public outreach, and active community involvement.